A "guerra" nas palavras : uma análise crítica da metáfora conceptual na retórica do presidente G. W. Bush Jr e de seus colaboradores - Carvalho, Sérgio Nascimento de (2006)
Based on the theoretical principles proposed by Lakoff and Johnson (1980/2002) this thesis aims at investigating, under a critical perspective (CHARTERIS-BLACK, 2004, 2005), the conceptual metaphors that transform, discursively, facts and/or events into acts of war . We hypothesize that these metaphors are, freque ntly, used, cognitively and linguistically, to justify an action or (re) action with clear political implications. The starting point of this research is the terrorist attacks of September 11 (known as 09/11) passing by the periods that anteceded the wars of Afghanistan and Iraq. The study investigates how the conceptualization of 09/11 as an act of war , realized by different materialization in discourse, was a relevant instrument in the process of justifying those wars. This conceptual frame, supported by other conceptual metaphors related to war, can be evidenced, discursively, by the speeches of President Bush and those of his collaborators. These speeches were reported directly or indirectly, in the national and international media. This analysis aims at exploring these speeches in a journalistic corpus (articles from The New York Times published during that time) trying to reveal the conceptual metaphors, the scenarios (MUSOLFF, 2004) and the metaphorical systems (LAKOFF, 1991) that underlie them. We also attempt at showing how metaphors may play a relevant role in the formation and spread of ideology so important to political leadership since they legitimize, conceptually and linguistically, specific visions, or framings, which support specific interests (CHILTON, 1993, 2004). The research is based on the cognitive metaphorical theory (LAKOFF & JOHNSON, 1980/2002; LAKOFF, 1987, 1991, 2002, 2005; KÖVECSES, 2001, 2002; GIBBS & STEEN, 1994 and others) with emphasis on the perspectives that focus the socio-cultural (TOMASELLO, 1999; KÖVECES, 2005), discursive (CAMERON, 1999, 2003) and ideological (CHARTERIS-BLACK, 2004, 2005; CHILTON, 1993, 2004 and MUSOLFF, 2004) aspects of metaphor.